Iron dyshomeostasis and time-course changes in iron-uptake systems and ferritin level in relation to pro-inflammatory microglia polarization in sepsis-induced encephalopathy - Sharawy, Nivin; Imam, Ahmad Abdel-Aliem; Aboulhoda, Basma Emad; Khalifa, Mohamed Mansour; Morcos, George N. B.; Abd Algaleel, Waleed Ahmed; Moustafa, Passant E.; Abdelbaset, Marwan A.; Shoukry, Tarek (Frontiers in Physiology, 2022)
Encephalopathy is a frequent and lethal consequence of sepsis. Recently, a growing body of evidence has provided important insights into the role of iron dyshomeostasis in the context of inflammation. The molecular mechanisms underlying iron dyshomeostasis and its relationship with macrophage phenotypes are largely unknown. Here, we aimed to characterize the changes in iron-transporter and storage proteins and the microglia phenotype that occur during the course of sepsis, as well as their relationship with sepsis-induced encephalopathy. We used a cecal ligation and puncture (CLP) murine model that closely resembles sepsis-induced encephalopathy. Rats were subjected to CLP or sham laparotomy, then were neurologically assessed at 6 h, 24 h, and 3 days after sepsis induction. The serum and brain were collected for subsequent biochemical, histological, and immunohistochemical assessment. Here, an iron excess was observed at time points that followed the pro-inflammatory macrophage polarization in CLP-induced encephalopathy. Our results revealed that the upregulation of non-transferrin-bound iron uptake (NTBI) and ferritin reduction appeared to be partially responsible for the excess free iron detected within the brain tissues. We further demonstrated that the microglia were shifted toward the pro-inflammatory phenotype, leading to persistent neuro-inflammation and neuronal damage after CLP. Taken together, these findings led us to conclude that sepsis increased the susceptibility of the brain to the iron burden via the upregulation of NTBI and the reduction of ferritin, which was concomitantly and correlatively associated with dominance of pro-inflammatory microglia and could explain the neurological dysfunction observed during sepsis.